Concepções e práticas do ensino de leitura em inglês no ensino médio - O'Connell, Daniel Mateus [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
National and international indicators (ENEM, PISA) point out serious problems in the teaching and learning of reading in our native language in this country. In the case of foreign languages, the situation is even worse, especially regarding high schools where teaching is expected to prepare the student for entry into a labor market in which English is becoming increasingly important. Considering the unsatisfactory results regarding the teaching of English reading, as well as the scarcity of research on reading instruction geared specifically for this level of basic education, a research was proposed in order to identify the theoretical and methodological conceptions of two High School English teachers about the different models of reading and how they are present in their practice. Our theoretical framework included authors who dealt with the process of initial and continual training of foreign language teachers, as well as reading models and approaches to the teaching of foreign languages and pedagogical practice. In this qualitative, ethnographic research, the instruments used were: a) classroom observation of two public-school teachers in two cities in São Paulo, working in this level of education; b) semi-structured interviews with the teachers to identify their concepts on reading instruction and to clarify doubts about some aspects of the observed teaching practice; c) field notes; d) analysis of teaching materials used. The data obtained in the interview were categorized as follows: a) initial and continued teacher training; b) approach and didactic materials; c) reading conceptions and d) reading practices. The main results of the interview and classroom observation indicated: a) dissatisfaction with the initial training of both, regarding the relationship between theory and practice; b) lack of specific opportunities for the continual training of English language teachers; c) influence of experiences in the trajectory of the...

Indicadores nacionais e internacionais, como Exame Nacional do Ensino Médio (ENEM) e Programme for International Student Assessment (PISA) respectivamente apontam graves problemas no ensino-aprendizagem da leitura em língua materna no país. No caso da língua estrangeira, a situação é ainda mais preocupante, principalmente no ensino médio, nível escolar em que se espera preparar o aluno para a inserção no mercado de trabalho, onde o inglês ocupa um lugar cada vez mais importante em nosso país. Tendo em vista os resultados insatisfatórios no ensino de leitura em língua inglesa, bem como a escassez de investigações sobre o ensino da leitura voltadas especificamente para esse nível da educação básica, esta pesquisa teve como objetivo identificar as concepções teórico-metodológicas de duas professoras de Inglês do Ensino Médio sobre os diferentes modelos de leitura e como elas se fazem presentes em sua prática. Nosso referencial teórico incluiu autores que trataram do processo de formação inicial e continuada de professores de línguas estrangeiras, de modelos de leitura, das abordagens de ensino de línguas estrangeiras bem como da prática pedagógica. Nesta pesquisa qualitativa, de cunho etnográfico, os instrumentos utilizados foram: a) observação de aulas de duas professoras da rede pública de duas cidades do interior paulista, atuando nesse nível de ensino; b) entrevistas semiestruturadas com as professoras para identificar suas concepções sobre ensino de leitura, bem como para esclarecer dúvidas sobre aspectos da prática pedagógica observada; c) caderno de campo; d) análise do material didático utilizado. Os dados obtidos na entrevista foram agrupados nas seguintes categorias: a) formação inicial e continuada de professores; b) abordagem e material didático; c) concepções de leitura; e d) práticas de leitura. Os principais resultados referentes à entrevista e à observação de aulas indicaram...
Keywords: Educação; Leitura; Ensino; Ensino médio; Língua inglesa; Education